Legal Consequences For Notaries Who Corruption Criminal Acts - Widyaningrum, Lendy (CV. Inara, 2022)
A notary is a public official who is authorized to make an authentic deed and has other authorities as referred to in paragraph (1)Invite-Law Number 30 of 2004 concerning the Position of a Notary (UUJN) as amended by Law Number 2 of 2014. The purpose of this study is to identify and analyze the legal consequences for a notary who commits a criminal act of corruption. In the Criminal Code, it is known that there are additional types of criminal acts, namely the additional criminal revocation of certain rights, although not all crimes committed by a Notary can be added to an additional penalty. However, it is different from the provisions in the Corruption Crime Act which stipulates that state administrators who commit criminal acts of corruption can have their rights revoked